Cost-effectiveness and budget impact analysis of infliximab and its biosimilar in patients with refractory moderate-to-severe Crohn's disease using real world evidence in Thailand. (1st November 2020) - Phisalprapa, Pochamana; Kositamongkol, Chayanis; Limsrivilai, Julajak; Aniwan, Satimai; Charatcharoenwitthaya, Phunchai; Pisespongsa, Pises; Kitiyakara, Taya; Treepongkaruna, Suporn; Chaiyakunapruk, Nathorn
Abstract: Aims: This study aimed to conduct a cost-effectiveness analysis of infliximab and its biosimilar compared to conventional therapy in refractory moderate-to-severe Crohn's disease (CD) in Thailand. Materials and methods: A Markov model was used to estimate lifetime costs and health benefits of infliximab from a societal perspective. Our analyses consisted of three choices of treatment (conventional therapy, infliximab originator, and biosimilar) and three treatment scenarios (infliximab 2 years and 3 years if relapse, infliximab 2 years and lifelong if relapse, and infliximab lifelong). The input parameters were obtained from the CD registry and systematic literature reviews. The results were reported as incremental cost-effectiveness ratios (ICERs) in 2017 USD per quality-adjusted life year (QALY) gained. The sensitivity analyses were performed to assess the influence of parameter uncertainty. Threshold sensitivity analyses were carried out to determine the optimal drug prices. Finally, budget impact analyses were conducted. Results: None of the scenarios was cost-effective at Thai willingness-to-pay threshold (4, 706 USD/QALY gained). The lowest ICER of 30, 121 USD/QALY gained was reported in the scenario that included only standard dose of infliximab biosimilar with the maximum of 5-year treatment. The drug prices need to be reduced by at least 72% to allow infliximab biosimilar to be cost-effective. The 5-year budget impact was only 695, 958 USD for the current biosimilar price. Conclusions: Infliximab for the treatment of refractory moderate-to-severe CD in Thailand would be cost-effective if the drug prices were significantly decreased. The best value for money strategy was infliximab biosimilar with a restricted duration of treatment. Key points: The use of infliximab and its biosimilar in a restricted duration of maximum 5-year is not cost-effective for patients with moderate-to-severe Crohn's disease refractory to conventional therapy, unless their price was lowered around 72–90% in Thailand. The estimated budget impact for adopting infliximab or its biosimilar for such indication has potential financial feasibility. Policy makers may consider cost-effectiveness and budget impact findings as well as other aspects such as rarity of disease as a part of the decision making process.